2015
DOI: 10.1016/j.str.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Parsimony in Protein Conformational Change

Abstract: Summary Protein conformational change is analyzed by finding the minimalist backbone torsion angle rotations that superpose crystal structures within experimental error. Of several approaches to enforcing parsimony during flexible least-squares superposition, an ℓ1-norm restraint provided greatest consistency with independent indications of flexibility from NMR relaxation dispersion and chemical shift perturbation in arginine kinase, and four previously studied systems. Crystallographic cross-validation shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Hinges identified from comparison of the crystal structures were broadly consistent with sites of NMR relaxation exchange that could be indicating intrinsic conformational fluctuation (Chapman et al, 2015; Davulcu et al, 2009). Furthermore, NMR residual dipolar couplings indicated that the average substrate-free solution structure is somewhat intermediate between the two crystal structures (Niu et al, 2011).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Hinges identified from comparison of the crystal structures were broadly consistent with sites of NMR relaxation exchange that could be indicating intrinsic conformational fluctuation (Chapman et al, 2015; Davulcu et al, 2009). Furthermore, NMR residual dipolar couplings indicated that the average substrate-free solution structure is somewhat intermediate between the two crystal structures (Niu et al, 2011).…”
Section: Discussionmentioning
confidence: 52%
“…The effects of local changes upon ADP alignment were examined by comparing the ambient temperature ADPs not just to the differences in atomic positions (Table 2), but to the changes in the form I TSA structure when it was superposed onto the substrate-free structure. Superposition was either flexible, using parsimoniously restrained changes to backbone dihedrals (smoothing out local changes), or constrained as rigid groups, using the TLS groupings (Chapman et al, 2015). Improvement in ADP alignment was modest, 1° and 2° respectively for the flexible and rigid-group superpositions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations